2020
DOI: 10.3390/polym12092039
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Copper(II) Sulfate in Ionically Cross-Linked Chitosan by Spray Drying for the Development of Irreversible Moisture Indicators in Paper Packaging

Abstract: Copper(II) sulfate-loaded chitosan microparticles were herein prepared using ionic cross-linking with sodium tripolyphosphate (STPP) followed by spray drying. The microencapsulation process was optimal using an inlet temperature of 180 °C, a liquid flow-rate of 290 mL/h, an aspiration rate of 90%, and an atomizing gas flow-rate of 667 nL/h. Chitosan particles containing copper(II) sulfate of approximately 4 µm with a shrunken-type morphology were efficiently attained and, thereafter, fixated on a paper substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…It can be observed that CNCs were mainly in the form of shrunken particles with a wide particle size distribution ( Figure 1 c). This particular type of morphology is known to occur during spray-drying due to the rapid evaporation of the solvent and the formation of an external crust during the first stages of drying, which collapses when the solvent present in the inner parts of the droplet evaporates and leads to a partial shrinkage of the particle [ 72 ]. It can also be observed that particle sizes varied from large particles of nearly 20 µm down to nanoparticles below 100 nm.…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that CNCs were mainly in the form of shrunken particles with a wide particle size distribution ( Figure 1 c). This particular type of morphology is known to occur during spray-drying due to the rapid evaporation of the solvent and the formation of an external crust during the first stages of drying, which collapses when the solvent present in the inner parts of the droplet evaporates and leads to a partial shrinkage of the particle [ 72 ]. It can also be observed that particle sizes varied from large particles of nearly 20 µm down to nanoparticles below 100 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The preparation of electrospun functional membrane can be realized in three ways. Polymers with functions, such as adsorption, can be directly used to prepare electrospun functional nanofibers; the functional substances can be added into the working fluid to prepare the electrospun functional fiber membrane; the prepared electrospun fiber membrane can be endowed with membrane function by post-treatment techniques such as coating [ 107 , 108 ], heat treatment [ 109 , 110 ] and cross-linking [ 111 , 112 , 113 , 114 ]. (2) The prepared fiber membrane needs to be hydrophilic but insoluble in water.…”
Section: Electrospun Functional Fiber Membrane For Antibiotic Remomentioning
confidence: 99%
“…The use of electrospun membranes in the treatment of wastewater contaminated with emerging pollutants such as antibiotics has been studied intensively in recent years. Thus, it is possible to establish, on the basis of the results presented so far in the literature, specific conditions that need to be met when using electrospun membranes [34,[108][109][110][111][112][113][114][115] It is important that the polymer used to obtain the fibers to be used as membranes be environmentally friendly, biodegradable, and without secondary environmental pollution. Additionally, the obtained membranes have to possess selectivity for the target pollutants, which can be developed by functionalization with specific groups.…”
Section: Principles Characteristics Parametersmentioning
confidence: 99%
“…Additionally, the obtained membranes have to possess selectivity for the target pollutants, which can be developed by functionalization with specific groups. Thus, the polymers used for electrospinning can be adsorbent, and can be used as such; additionally, substances possessing specific adsorbent functional groups can be added to the electrospinning solution, or the obtained membrane can be subjected to post-treatment techniques after the electrospinning process, such as coating [108,109], heat treatment [110,111], and cross-linking [112][113][114][115].…”
Section: Principles Characteristics Parametersmentioning
confidence: 99%